Ironic depiction of being wise in search of Wisdom : a socio-rhetorical study of the Elihu speeches in Job 32-37 - Musa, Hassan (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.